2003
DOI: 10.1002/bjs.4123
|View full text |Cite
|
Sign up to set email alerts
|

Impact of anatomical wrap position on the outcome of Nissen fundoplication

Abstract: Anatomical repair during antireflux surgery does not stand the test of time. Although this has no demonstrable influence on the subjective outcome, the authors do not recommend deviating from well designed surgical guidelines. Current theories on the mechanism of antireflux surgery require further evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 29 publications
2
17
1
Order By: Relevance
“…18 What our study has shown, however, is that objective evidence of anatomical failure does not appear to correlate with subjective recurrence of symptoms. This finding is in agreement with that from Donkervoort et al, 17 who also reported that the repair did not stand the test of time anatomically in 55% of patients but with no demonstrable influence on subjective outcome. It is possible that the proportional increase in interclip distance (25% and 50%) may be too rigorous owing to the possible lie of the wrap marker clips, although similar variation in lie is not possible for the crural clips.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…18 What our study has shown, however, is that objective evidence of anatomical failure does not appear to correlate with subjective recurrence of symptoms. This finding is in agreement with that from Donkervoort et al, 17 who also reported that the repair did not stand the test of time anatomically in 55% of patients but with no demonstrable influence on subjective outcome. It is possible that the proportional increase in interclip distance (25% and 50%) may be too rigorous owing to the possible lie of the wrap marker clips, although similar variation in lie is not possible for the crural clips.…”
Section: Discussionsupporting
confidence: 93%
“…Donkervoort et al 17 undertook barium swallows at 2 years' postoperatively as part of their follow-up, which is a commendable time period. We have noticed a progressive reduction in the number of patients willing to attend followup appointments (18 patients in this study).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations